Suburban Practices of Energy Descent. (22nd July 2020) - Alexander, Samuel; Gleeson, Brendan
Abstract: This article proceeds on the basis that the cost of energy will rise in coming years and decades as the age of fossil energy abundance comes to an end. Given the close connection between energy and economic activity, we also assume that declining energy availability and affordability will lead to economic contraction and reduced material affluence. In overconsuming and overdeveloped nations, such resource and energy "degrowth" is desirable and necessary from a sustainability perspective, provided it is planned for and managed in ways consistent with basic principles of distributive equity. Working within that degrowth paradigm, we examine how scarcer and more expensive energy may impact the suburban way of life and how households might prepare for this very plausible, but challenging, energy descent future. The article examines energy demand management in suburbia and how the limited energy needed to provide for essential household services can best be secured in an era of expensive energy and climate instability. After reviewing various energy practices, we also highlight a need for an ethos of sufficiency, moderation, and radical frugality, which we argue is essential for building resilience in the face of forthcoming energy challenges and a harsher climate.